Sustainable vehicle routing based on firefly algorithm and TOPSIS methodology. (2019) - Micale, R.; Marannano, G.; Giallanza, A.; Miglietta, P.P.; Agnusdei, G.P.; La Scalia, G.
Abstract: In a sustainable management of logistics, transportation plays a crucial role. Traditionally, the main purpose was to solve the Vehicle Routing Problem minimizing the cost associated with the travelled distances. Nowadays, the economic profit cannot be the only driver for achieving sustainability and environmental issues have to be also considered. In this paper, to satisfy the intricate limits involved in real vehicle routing problem, the study has been structured considering different types of vehicles in terms of maximum capacity, velocity and emissions, asymmetric paths, vehicle-client constraints and delivery time windows. The firefly algorithm has been implemented to solve the vehicle routing problem and the TOPSIS technique has been applied to integrate economic and environmental factors. Finally, to prove the effectiveness of the proposed approach, a numerical example has been proposed using data provided by a logistic company located in Sicily.